2018
DOI: 10.3389/fcimb.2018.00075
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a New Phage Integration Vector pFIV-Val for Use in Different Francisella Species

Abstract: We recently identified and described a putative prophage on the genomic island FhaGI-1 located within the genome of Francisella hispaniensis AS02-814 (F. tularensis subsp. novicida-like 3523). In this study, we constructed two variants of a Francisella phage integration vector, called pFIV1-Val and pFIV2-Val (Francisella Integration Vector-tRNAVal-specific), using the attL/R-sites and the site-specific integrase (FN3523_1033) of FhaGI-1, a chloramphenicol resistance cassette and a sacB gene for counter selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…This would be a fruitful undertaking, as it could be shown that F-W12 is genetically treatable (generation of mutant strains by a transposon or of specific mutants by site-specific recombination after natural transformation; transformation of plasmids by electroporation). Recently, a new phage integration vector (pFIV-Val) was built, which can be used for integrating genes into the genome of F-W12, as well as for the complementation of specific mutant strains [ 80 , 81 , 82 ].…”
Section: Francisella Sp Strain W12-1067 (F-w12mentioning
confidence: 99%
“…This would be a fruitful undertaking, as it could be shown that F-W12 is genetically treatable (generation of mutant strains by a transposon or of specific mutants by site-specific recombination after natural transformation; transformation of plasmids by electroporation). Recently, a new phage integration vector (pFIV-Val) was built, which can be used for integrating genes into the genome of F-W12, as well as for the complementation of specific mutant strains [ 80 , 81 , 82 ].…”
Section: Francisella Sp Strain W12-1067 (F-w12mentioning
confidence: 99%
“…Two hypothetical proteins (Fhv_0032/49) and two integrases (Fhv_0033/51) exhibit homologs (29–62% identity) to proteins in Fno , Fph and F. salina . The protein Fhv_0051 has been identified earlier to be the site-specific integrase of FhaGI-1, necessary for the integration and excision of the phage integration vector pFIV-Val and thus probably also for the prophage [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Francisella strains were cultivated at 37 °C in medium T (MT) (1% brain heart infusion broth (Difco Laboratories, Inc., Sparks, MD, USA), 1% bacto tryptone (Difco Laboratories, Inc., Sparks, MD, USA), 1% technical casamino acids (Difco Laboratories, Inc., Sparks, MD, USA), 0.005% of MgSO 4 , 0.01% FeSO 4 , 0.12% sodium citrate, 0.02% KCl, 0.04% K 2 HPO 4 , 0.06% L-cysteine and 1.5% glucose) [ 32 , 33 ] or on MT agar plates supplemented with hemoglobin and charcoal (MTKH plates, [ 19 ]). E. coli strains were grown at 37 °C in lysogeny broth (LB; 1% bacto tryptone, 0.5% yeast extract, 0.5% NaCl) or on LB agar (LB supplemented with 1.2% agar).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transduction: Transduction is the transfer of DNA to a bacterium via a bacteriophage. There have been only a few reports of bacteriophage which can act against Francisella so far ( Koliaditskaia et al, 1959 ; Tlapak et al, 2018 ) and they appear so far to be unstable or difficult to isolate. This area of research is ongoing, but one very interesting finding was the identification of CRISPR/CAS9 system in F. novicida ( Schunder et al, 2013 ), suggesting that there have been bacteriophage interactions with Francisella in the past, enough to acquire a viral immunity system such as CRISPR/Cas.…”
Section: Horizontal Gene Transfer In Francisellamentioning
confidence: 99%